PEMBUATAN SOSIS KACANG TUNGGAK DENGAN PENAMBAHAN GLUTEN DAN CURD LIMBAH PENGOLAHAN VOC (Jurnal Teknologi Pangan, 2018)
PEMBUATAN SOSIS KACANG TUNGGAK DENGAN PENAMBAHAN GLUTEN DAN CURD LIMBAH PENGOLAHAN VOC